(untitled) (Journal of Asian Development Studies, 2026)
This thesis examines how the pursuit of human rights and upward mobility leads to tragedy rather than fulfilment for a subaltern woman in Dur e Aziz Amna’s A Splintering (2025). It focuses on Tara, a young woman from a poor family in rural Punjab, Pakistan. This study applies Ratna Kapur’s human rights critique to explain how Tara’s ambition shifts from aspirational to avaricious and how she becomes what Kapur calls a “failed or unhappy subaltern subject.” The concept of the “failed or unhappy subaltern subject” has been studied in human rights scholarship, but this investigation applies it specifically to a contemporary Pakistani novel, thereby filling a significant gap in the literature. The analysis, which is qualitative in nature, applies Kapur’s theoretical framework to argue that the acquisition of human rights represents the “terminal limits” of what rights can achieve rather than the moment of liberation. The main argument is that Tara’s upward mobility does not lead to freedom and happiness but instead to despair and moral corruption. Human rights, as Kapur argues, cannot produce meaningful happiness for subaltern subjects